Training in Nigerian art schools: a critique of gender distribution - Abodunrin, Johnson Adelani (Harmonia: Journal of Arts Research and Education, 2017)
Training is indispensable in all facets of life in order to further knowledge and skills irrespective of gender difference, yet this disparity has become a phenomenon in artistic practice in Nigeria. The study aimed at examining art training in relation to gender distribution into various areas of specialization in art schools in Nigeria. There has been a gender imbalance in various areas of specialization which has left certain areas for male and female. Data for this study were collected in art School in Southwestern Nigeria between 2011/2012 to 2014/2015 academic sessions using archival materials to know the gender affinities. The university selected as sample size within the geographical scope of the study is Ladoke Akintola University of Technology, Ogbomoso. The selection was based on the orientation of their training and admission criteria which differs tremendously. Descriptive analysis was adopted to know the gender affiliation in the practice. Finding reveals that the total enrollments of students are more of females (55.8%) than male (45.2%) are admitted to study art. The result has also shown that more female (93.3%) specializes in textile while more male (84%) students are in sculpture. This perhaps could be attributed to the nature and the demands of each area of specialization. Textile design attracts more female artist because of; the socio-cultural affiliation of the discipline, interest in fashion; the readily available market for textile wares across all social class and the less demand on draughtsmanship skills as compared to other forms of arts.